Por que as taxas de juros são tão elevadas no Brasil? : uma avaliação empírica - Oreiro, José Luís da Costa (2012)
This paper aims at exploring some hypothesis to explain why real interest rate and bank spread are so high. We argue that the interest rate problem and bank spread problem are connected. More precisely, one important cause of bank spread is the high level of BCB interest rate. So, the solution of interest rate problem, so that it can converge to the levels observed in other countries, will help to reduce bank spread, and doing so contributing to the reduction of the capital cost of the Brazilian economy.